From ‘Post-Industrial’ to ‘Network Society’ and Beyond: The Political Conjunctures and Current Crisis of Information Society Theory - Marko Ampuja; Juha Koivisto (tripleC: Communication, Capitalism & Critique)
This article critically discusses the intellectual and conceptual shifts that have occurred in information society theories (and also policies) in the previous four decades. We will examine the topic by focusing on the work of Daniel Bell and Manuel Castells, arguably two of the most important information society theorists. A key element in the academic shift from “post-industrial” (Bell) thinking to the discourse on “network society” (Castells) is that it has brought forward a different way of understanding the role of the state vis-a-vis the development of new information and communication technologies, as well as a new assessment of the role of the state in the economy and society at large. Against the Keynesian undertones of Bell’s ideas, Castells’ network society theory represents a neoliberally restructured version of “information society” that is associated with the rise of flexibility, individuality and a new culture of innovation. We argue that these changing discourses on the information society have served a definite hegemonic function for political elites, offering useful ideals and conceptions for forming politics and political compromises in different historical conjunctures. We conclude the article by looking at how the on-going global economic crisis and neoliberalism’s weakening hegemonic potential and turn to austerity and authoritarian solutions challenges existing information society theories.